2014
DOI: 10.1161/jaha.114.001380
|View full text |Cite
|
Sign up to set email alerts
|

Validated Contemporary Risk Model of Acute Kidney Injury in Patients Undergoing Percutaneous Coronary Interventions: Insights From the National Cardiovascular Data Registry Cath‐PCI Registry

Abstract: BackgroundWe developed risk models for predicting acute kidney injury (AKI) and AKI requiring dialysis (AKI‐D) after percutaneous coronary intervention (PCI) to support quality assessment and the use of preventative strategies.Methods and ResultsAKI was defined as an absolute increase of ≥0.3 mg/dL or a relative increase of 50% in serum creatinine (AKIN Stage 1 or greater) and AKI‐D was a new requirement for dialysis following PCI. Data from 947 012 consecutive PCI patients and 1253 sites participating in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 182 publications
(181 citation statements)
references
References 43 publications
5
170
2
4
Order By: Relevance
“…4,15 In our analysis, we expand on these findings by identifying blood transfusion and bleeding as other strong predictors of AKI in PCI patients. In a comparative assessment, we demonstrated that blood transfusion was the strongest predictor of AKI in patients with anemia at baseline and without a postprocedure bleeding event and in patients without anemia at baseline but who did suffer a bleeding event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,15 In our analysis, we expand on these findings by identifying blood transfusion and bleeding as other strong predictors of AKI in PCI patients. In a comparative assessment, we demonstrated that blood transfusion was the strongest predictor of AKI in patients with anemia at baseline and without a postprocedure bleeding event and in patients without anemia at baseline but who did suffer a bleeding event.…”
Section: Discussionmentioning
confidence: 99%
“…Variables included in the model were age, preprocedure creatinine, prior cerebrovascular disease, prior heart failure, diabetes mellitus, anemia (hemoglobin <10 mg/dL), weeks HF, intraaortic balloon pump before procedure, and contrast volume, based on previously developed CathPCI registry models for post-PCI AKI. 4,15 The unadjusted and adjusted odds ratios (ORs) of the association of blood transfusion with AKI for the overall sample and the subgroups (ST-segment-elevation myocardial infarction, and unstable angina/non-ST-segment-elevation myocardial infarction ) are presented. In addition, analysis was performed to determine the association between blood transfusion and AKI among patients who did or did not have reported postprocedure bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…We repeated each of these analyses for the secondary outcomes of bleeding complications at 72 hours using a validated predictive model for bleeding,(19) and new requirement for dialysis using a validated predictive model for post-PCI renal failure. (20) For all analyses, an OR < 1 indicates that lower PCI operator volume is associated with lower odds of the outcome compared with higher operator volume, and an OR > 1 indicates that lower PCI operator volume is associated with higher odds of the outcome compared with higher operator volume.…”
Section: Methodsmentioning
confidence: 99%
“…3). Multivariate Cox-regression models using established risk factors for MAKE [27], that were significantly different in the observed cohort stratified into no MAKE or MAKE (Table 3), were calculated to demonstrate an independent association between plasma kynurenine ≥ 3.5 µmol/L and an elevated risk for MAKE (Table 5). Model A used baseline GFR, congestive heart failure, anemia, age, contrast media volume, elective or emergency coronary angiography, and current smoking status as covariates (chi-squared=33.250, p=0.00002) .…”
Section: Resultsmentioning
confidence: 99%